COVID-19: using chest CT of major trauma patients to monitor and evaluate the second wave in London and the development of routine monitoring in practice. Issue 3 (March 2022) - Grubnic, S.; Hine, J.; Adam, E.J.; Patel, J.; Moser, J.; Phillips, C.; Webb, P.; Blanks, R.
Abstract : AIM: To follow-up previous work evaluating incidental findings of COVID-19 signs on computed tomography (CT) images of major trauma patients to include the second wave prior to any major effects from vaccines. MATERIALS AND METHODS: The study population included all patients admitted following major trauma between 1 January 2020 and 28 February 2021 with CT including the lungs ( n =1776). Major trauma patients admitted pre-COVID-19 from alternate months from January 2019 to November 2019 comprised a control group ( n =837). The assessing radiologists were blinded to the time period and used double reading in consensus to determine if the patient had signs of COVID-19. Lung appearances were classified as no evidence of COVID-19, minor signs, or major signs. RESULTS: The method successfully tracked the second wave of the COVID-19 pandemic in London. The estimated population affected by the disease based on those with major signs was similar to estimates of the proportion of the population in London with antibodies (around 30% by end February 2021) and the total of major and minor signs produced a much higher figure of 68%, which may include all those with both antibody and just T-cell responses. CONCLUSIONS: Incidental findings on CT from major trauma patients may provide a novel and sensitive way of tracking the virus. It is recommended that all major trauma units include a simple question on signs of COVID-19 to provide an early warning system for further waves. Highlights: Incidental findings on trauma CT scans successfully tracked the COVID 19 second wave. Proportion of population with major CT signs is similar to proportion with antibodies. Proportion with major and minor signs may include those with antibody and T-cell responses. Trauma scans may provide an early warning system for further waves or future pandemics.